Specific Features of Formation of Laser‐Induced Periodic Surface Structures on Ge2Sb2Te5 Amorphous Thin Films under Illumination by Femtosecond Laser Pulses. Issue 11 (14th July 2020) - Kozyukhin, Sergey; Smayev, Mikhail; Sigaev, Vladimir; Vorobyov, Yuri; Zaytseva, Yuliya; Sherchenkov, Alexey; Lazarenko, Petr
Abstract : This article presents the results of irradiation treatment by the 180 fs laser pulses at the wavelength of 1030 nm of Ge2 Sb2 Te5 amorphous thin films. It is shown that high‐quality laser‐induced periodic surface structures (LIPSS) are formed at certain parameters of irradiation with a period corresponding to the laser wavelength. A distinctive feature of the observed LIPSS is the alternation of amorphous and crystalline regions corresponding to the ridges and valleys of the periodic structures which are perpendicular to the polarization of the femtosecond light beam. These surface crystalline–amorphous alternating structures are characterized by significantly less pronounced surface relief than for previously observed LIPSS formed by femtosecond laser pulses at the wavelength of 515 nm. Possible mechanisms are considered for the LIPSS formation including the formation of surface plasmon polariton and its subsequent interference with the incident beam resulting in spatial modulation of the temperature on the film surface. As the results indicate, the formation of alternating structure has a threshold nature with the threshold laser fluence for LIPSS formation depending logarithmically on the number of laser pulses, which is attributed to the transient nature of the crystallization process. Abstract : High‐quality laser‐induced periodic surface structures (LIPSS) are formed under irradiation of Ge2 Sb2 Te5 amorphous thin films by 180 fs laser pulses at the wavelength of 1030 nm. A distinctive feature of the LIPSS is the alternation of amorphous and crystalline regions. The formation of the alternating structure has a threshold nature.